Investigating persuasive writing by 9–11 year olds. (2nd September 2016) - Beard, Roger; Burrell, Andrew; Homer, Matt
ABSTRACT: Within research into children's persuasive writing, relatively little work has been done on the writing of advertisements, how such writing develops in the primary school years and the textual features that help to secure this development. Framed within rhetoric, writing and linguistics, an exploratory study was undertaken in which a standardised task and a repeat-measures design were used to investigate the writing of an advertisement by 112 9–10-year-old pupils from two English Local Authorities, undertaken in the spring term and again a year later. The scripts were first rated for five generic constituents of writing using the standardised task guidelines. The scripts were then rated for the use of specific textual features of advertisements. All constituents, and many textual features, showed increased use across the sample as a whole, even though further analysis showed that some children who had used certain features in Year 5 had not used them in Year 6. Qualitative analysis revealed common features within attainment subgroups in content, language use and overall effectiveness of the writing. There were indications that, if appropriately supported, experience of advertisement writing could contribute to children's abilities in tackling other forms of persuasive writing.